IMPLEMENTATION OF AER IWAK MEDIA AS AN EFFORT TO INCREASE MOTIVATION AND LEARNING OUTCOMES OF PAUD STUDENTS IN WEST SUMBAWA DISTRICT - Silvia Dewi, Yuyun; umar, Umar; Fahlia, Fahlia (Jurnal Manajemen Pelayanan Hotel, 2022)
This study discusses the application of Iwak Aer media as an effort to improve student learning outcomes for Early Childhood Education (PAUD) in West Sumbawa Regency. The research objectives are 1) to produce a model of Iwak Aer which is used as a learning tool and media for PAUD students in West Sumbawa Regency. 2) to test and implement Iwak Aer as a learning tool and media for PAUD students in West Sumbawa Regency. 3) to determine the effectiveness of Iwak Aer as a learning tool and media in improving the learning outcomes of PAUD students in the West Sumbawa Regency. This type of research includes the type of development research, using experimental methods. The development of Iwak Aer was tested on a small scale at PAUD Negeri 1 Brang Ene with a sample of 25 students. Validation of media experts by 4 expert validators with details, namely 2 validators from supervisors and 2 validators from PAUD Negeri 1 Brang Ene teachers. Methods of data collection using observation techniques, interviews with the help of questionnaires/ questionnaires, interview sheets, and observation sheets. The results showed the score on the PreTest with details of the number of students who got the very well developed category at 0%, developed as expected by 8%, started to develop by 72%, and did not develop by 20%. The average value on the Post-Test with details of the number of students who got the very well developed category was 36%, developed as expected by 56%, started to develop by 8%, and has not developed by 0%. The conclusion of this research is the Iwak Aer model which is used as a learning tool and media for PAUD students in West Sumbawa Regency. The results of the test or implementation of Iwak Aer as a learning tool and media for PAUD students in the West Sumbawa Regency. Iwak Aer as a learning tool and media can improve the learning outcomes of PAUD students in the West Sumbawa Regency. Keywords: Motivation, Learning Outcomes, Media Iwak AER, and Age Children Early